KONFLIK KEAGENAN: HUBUNGAN SIMULTAN KEPEMILIKAN MANAJERIAL, KEBIJAKAN UTANG, DAN KEBIJAKAN DIVIDEN - Fitri Susilowati; Eduardus Tandelilin (University of Merdeka Malang, 2015)
The main purpose of this research was to determine the agency theory in Indonesia capital market. The variableof agency conflict was represented by asset utility variable, while controlling the agency conflicts mechanismwas represented by the managerial ownership, leverage, and dividend. The secondary data used in this researchwas drawn from the Indonesia Capital Market Directory (ICMD) and Blommberg. The sample datawere limited at the manufacture companies and non-financial services, and they were listed on the IndonesiaStock Exchange (BEI). The research method approach used was quantitative method. The time period of thedata was year to year from 2000 to 2011. The instrument of analysis was seemingly unrelated regression(SUR), with panel data and simultaneous model regression techniques. The result of this research was that themanagerial ownership had a positive and significant effect on performance. Debt policy had a positive effectbut not significant to performance, so 1b hypothesis was not accepted. Dividend policy had a positive andsignificant effect on performance. Simultaneously there was a substitution and interdependence relationshipbetween the managerial ownership and debt policy. The relationship between two variables namely the managerialownership and dividend policy could not be concluded.